2012
DOI: 10.1007/s10517-012-1788-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxidized Dextran on Reparative Regeneration of the Skin after Burn Injury

Abstract: In adult Wistar rats, a 3B degree skin burn was modeled and treated by daily application of 5% aqueous solution of oxidized dextran (molecular weight of 60 kDa) on the wound surface. In animals treated with oxidized dextran, neutrophil count in the connective tissue adjacent to the wound increased by day 5 and then decreased by day 21 after burn infliction; proliferation of fibroblasts was observed later than in untreated animals, in whom inflammation run a subacute course. Oxidized dextran increased the conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…These data suggest that the composition with OD modulates the functional state of the fi broblasts and suppresses their collagen-synthetic ability. This antifi brotic activity of OD was previously observed during treatment of generalized tuberculosis in mice with a composition of isonicotinic acid hydrazide with OD: fi brotic complications of experimental tuberculosis decreased by more than 4 times in the liver, by more than 3 times in the lymph nodes, and by 28% in the lungs [3,7] in comparison with treatment with isonicotinic acid hydrazide alone.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…These data suggest that the composition with OD modulates the functional state of the fi broblasts and suppresses their collagen-synthetic ability. This antifi brotic activity of OD was previously observed during treatment of generalized tuberculosis in mice with a composition of isonicotinic acid hydrazide with OD: fi brotic complications of experimental tuberculosis decreased by more than 4 times in the liver, by more than 3 times in the lymph nodes, and by 28% in the lungs [3,7] in comparison with treatment with isonicotinic acid hydrazide alone.…”
Section: Resultssupporting
confidence: 66%
“…Grade IIIB burn usually heals with dense scar, which, depending on the area of burn, may result in the formation of contractures. It has been previously shown that oxidized dextran (OD) with lower oxidation degree than OD used in this work was captured by cells of different histogenesis including macrophages [4,5] and stimulated reparative cellular and intracellular responses in the liver and lungs [7], reparative regeneration of the skin [3] and had antifi brotic effect reducing scar area [3,5].…”
mentioning
confidence: 99%